2021
DOI: 10.1155/2021/9621572
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and COVID-19: Emphasis on Adequate Asthma Control

Abstract: Asthmatics are at an increased risk of developing exacerbations after being infected by respiratory viruses such as influenza virus, parainfluenza virus, and human and severe acute respiratory syndrome coronaviruses (SARS-CoV). Asthma, especially when poorly controlled, is an independent risk factor for developing pneumonia. A subset of asthmatics can have significant defects in their innate, humoral, and cell-mediated immunity arms, which may explain the increased susceptibility to infections. Adequate asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 150 publications
(159 reference statements)
1
10
0
Order By: Relevance
“…Asthma is a heterogeneous immunopathological disease, with features of chronic inflammation, airway hyperresponsiveness, mucus over secretion, and airway remodeling. 1 , 2 Estimates of the global prevalence of asthma in different populations range from 1% to 18% and as many as 300 million people have asthma globally with increasing annual cost to the healthcare system. 12 According to GINA, the diagnosis of asthma should be based on the patient's clinical symptoms combined with laboratory evidence of BPT or BDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is a heterogeneous immunopathological disease, with features of chronic inflammation, airway hyperresponsiveness, mucus over secretion, and airway remodeling. 1 , 2 Estimates of the global prevalence of asthma in different populations range from 1% to 18% and as many as 300 million people have asthma globally with increasing annual cost to the healthcare system. 12 According to GINA, the diagnosis of asthma should be based on the patient's clinical symptoms combined with laboratory evidence of BPT or BDT.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma, which is characterized by airway hyperresponsiveness, airway eosinophilic inflammation, mucus overproduction, and airway remodeling, is gradually becoming an increasingly common disease. Airway eosinophilic inflammation is a central feature of asthma 1–3 . Asthma is a heterogenous disease with different phenotypes, including type 2‐low and type 2‐high asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Furthermore, asthma is regarded as a risk factor for the development of viral lower respiratory tract infections. [7] Of the respiratory comorbidities associated with COVID-19, it is observed that patients with chronic obstructive pulmonary disease are at a higher risk of having severe COVID-19. [8] As such, in the early phase of the pandemic, a similar relationship was predicted between asthma and COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Estimates of the global prevalence of asthma in different populations range from 1% to 18%, and as many as 300 million people have asthma globally with increasing annual cost to the health-care system. 3,4 Bronchial epithelium plays an important function in maintaining airway homeostasis, balancing repair, initiating airway inflammation and producing mucus in asthma due to its subtle role in regulating tolerance and specific immune responses. [5][6][7] Protein tyrosine phosphatases (PTP) family is involved in cellular functions in parthenogenesis of cancers including proliferation, differentiation and migration.…”
Section: Introductionmentioning
confidence: 99%